Nanostructured Systems for the Organelle-specific Delivery of Anticancer Drugs - Anselmo Joanitti, Graziella; Ganassin, Rayane; Correa Rodrigues, Mosar; Paulo Figueiro Longo, Joao; Jiang, Cheng-Shi; Gu, Jinsong; Milena Leal Pinto, Sandra; de Fatima Menezes Almeida dos Santos, Maria; Bentes de Azevedo, Ricardo; Alexandre Muehlmann, Luis (Mini Reviews in Medicinal Chemistry, 2017)
Nanotechnology has provided powerful tools to improve the chemotherapy of cancer. Different nanostructures have been developed which deliver the anticancer drugs more selectively to tumor than to healthy tissues. The result has generally been the increase in efficacy and safety of classical anticancer drugs. In recent years, several studies have focused not only on the delivery of anticancer drugs to tumors, but also on delivering the drugs to specific organelles of cancer cells. Endoplasmic reticulum, Golgi apparatus, lysosomes, mitochondria, and nucleus have been the targets of different nanostructured drug delivery systems developed with the goal of circumventing drugresistance, increasing drug efficacy, and so on. So far, the results described in the literature show that this strategy may be used to improve chemotherapy outcomes. In this review a discussion is presented on the strategies described in the literature to deliver anticancer drugs to specific organelles of cancer cells by using nanostructures.
Keywords: chemotherapy